Whole-exome sequencing reveals a novel frameshift and a recurrent nonsense SPG11 variant causing rare familial amyotrophic lateral sclerosis type 5 in two consanguineous Pakistani families - Riaz Ahmad; Muhammad Naeem; Henry Houlden (Molecular Biology Reports, 2026)
Background Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that affects both upper and lower motor neurons, disturbing communication between the brain and muscles. So far, few reports have been published for the SPG11 -associated ALS, and this is the first documented case from Pakistan. Methods We report a rare subtype of ALS with an autosomal recessive mode of inheritance with juvenile onset before 25 years of age in the five affected individuals from two unrelated families. Whole-exome sequencing was performed to identify disease-causing variants, and selected variants were further prioritized based on predicted pathogenicity and similarity to clinical phenotypes. Results Two homozygous variants within the SPG11 gene were identified as pathogenic according to the ACMG and ClinGen Sequence Variant Interpretation (SVI) Working Group recommendations: a novel truncation (NM_025137.4:c.6738dup, p.Glu2247Ter) variant as validated by Sanger sequencing and a recurrent nonsense (NM_025137.4: c.782C>A, p.Ser261Ter) variant (rs765477482) previously reported in a family affected with autosomal recessive hereditary spastic paraplegia (ARHSP). In silico prediction tools further confirmed their pathogenicity. Conclusion Five patients with juvenile-onset ALS born to consanguineous parents were found to have homozygous SPG11 gene variants. Our findings describe the overlapping phenotypes of SPG11 -related autosomal recessive juvenile ALS and ARHSP, suggesting that these disorders show a clear overlapping phenotype with common genetic defects. In clinical practice, it is challenging to distinguish between these two disorders. Additional Mendelian cases should be included to clarify further and investigate whether these represent two diverse diseases caused by variants in a single gene.